The world of worm - Grell, Ole Peter, author.
1 online resource.
Keywords: "This monograph offers the first comprehensive treatment of the multi-faceted scholarly interests of Ole Worm, professor of medicine at the University of Copenhagen. Scholarship about Worm has focused mainly on Worm's collecting and the creation of his cabinet of curiosity, the Museum Wormianum, resulting in Worm's rationale for his research being largely overlooked. Worm shared his many interests with a number of other physicians of the age, but in terms of breadth, few matched the variety of his concerns. For a man who considered himself first and foremost a physician and anatomist, his interests in Paracelsianism and collecting can at times be baffling, while his interests in antiquarianism, runes, and chronology strike the modern reader as at odds with his medical and natural philosophical interests. It is important to comprehend that Worm's multi-faceted interests in the created world was underpinned by his Lutheran, Melanchthonian natural philosophy, and this served to unify all Worm's scholarly undertakings, inquiries, and experiments in the single aim of reaching a better understanding of God's creation, the Book of Nature"--